Key aspects for developing your instructional materials (2004)
This article describes crucial aspects that EFL teachers must consider for the elaboration of materials to support the instructional design component of their classes. It also emphasizes that language educators should not only maintain a balance between theory and practice when developing their didactic resources, but they also should keep themselves updated in terms of the latest research in the language education field. The article also addresses key questions teachers should formulate before beginning the process of design, and provides useful ideas to develop dynamic, content enriching, and visually attractive materials. Key words: Course Design, Material Design, Motivational Design, Content Enriching Materials, Attractive Layouts, Teachers’ Creativity Este artículo describe aspectos cruciales que los docentes de inglés como lengua extranjera deben tener en cuenta para la elaboración de materiales de apoyo del componente de instrucción de sus clases. También enfatiza que los docentes de lengua extranjera no solamente deben mantener un balance entre la teoría y la práctica al desarrollar sus ayudas didácticas, sino que también deben mantenerse actualizados en términos de los más recientes avances de la investigación en el campo de la educación en lenguas. El artículo discute preguntas claves que los maestros deben formular antes de comenzar el proceso de diseño y brinda ideas útiles para el desarrollo de materiales con contenidos enriquecedores y que resulten dinámicos y atractivos visualmente. Palabras claves: Diseño de Cursos, Diseño de Materiales, Contenidos Enriquecedores, Esquemas Llamativos, Creatividad Docente